Hubungan antara perilaku picky eater dengan perkembangan motorik halus pada anak prasekolah - Nahira Nahira; Marliah Marliah; Nurjannah Supardi; Rosita Rosita (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Picky eating is a problem often encountered by parents that can lead to malnutrition if it persists over a long period of time. This eating disorder can have an impact on a child's growth, increase the risk of death, and if it becomes more severe, it can lead to anorexia and bulimia. In adulthood, this eating disorder can increase the risk of degenerative diseases and make individuals more susceptible to nutritional problems. Almost every component of a child's body can be trained through physical activity to move dynamically, preventing excessive fat formation and impacting nutritional status. Purpose: To determine the relationship between picky eating behavior and motor development in preschool children. Method: This study used a cross-sectional design, collecting samples from 35 toddlers using total sampling techniques. The respondents were all parents of students at the Kemala Bhayangkari 05 SPN Batua kindergarten. The research instruments used were the Developmental Pre-Screening Questionnaire (KPSP) and the Picky Eater Questionnaire. Results: The study showed that based on the chi-square statistical test, a p-value of 0.004 was obtained. Conclusion: There is a relationship between picky eating behavior and motor development in preschool children. Suggestion: Toddlers with picky eating conditions should be given special attention to address their condition so that it does not have a long-term impact.